Molekulardiagnostik des nichtkleinzelligen Lungenkarzinoms: neue Marker und Technologien - Warth, Arne; Endris, Volker; Kriegsmann, Mark; Stenzinger, Albrecht; Penzel, Roland; Pfarr, Nicole; Weichert, Wilko (Der Pathologe, 2015)
Lung cancer is the prototypical tumor entity for the development of new diagnostic and individualized therapeutic strategies based on molecular patient stratification. Developments in this field specifically concentrate on predictive biomarkers for the response to conventional therapeutic agents, novel drugs targeting specific mutations and also new immunomodulatory drugs. The multitude of upcoming new predictive biomarkers requires the development and implementation of efficient test strategies and comprehensive technical methods, specifically when tissue restrictions inherent to lung cancer diagnostics are also taken into account. Novel procedures and technical aspects of these issues are discussed in this review.
Gesehen am 27.09.2017